Electronically Signed Documents in Health Care - Hollerbach, A.; Brandner, R.; Bess, A.; Schmücker, P.; Bergh, B. (Methods of Information in Medicine, 2005)
Objectives: Our objectives were to analyze and assess data formats for their suitability for conclusive and secure long-term archiving and to develop a concept for legally secure transformation of electronically signed documents that are not available in data formats appropriate for long-term archiving.Methods: On the basis of literature review and Internet searches we developed general evaluation criteria to assess data formats with regard to their suitability for conclusive and secure long-term archiving. The assessment of data formats refers to format specifications and available literature. For the analyses of the transformation of signed documents we analyzed legal requirements on the basis of laws and ordinances as well as technical requirements by means of literature reviews, Internet searches and technical specifications.Results: The following evaluation criteria are suited for this kind of assessment of data formats: transparency and standardization, stability, presentation and secuity According to our assessment the following data formats are most suitable for conclusive and secure long-term archiving: PDF for formatted and unstructured text documents, XML for markup languages, TIFF for images in general, DICOM for medical images and S/MIME for the storage of e-mail. To transform electronically signed documents we propose an elementary procedure and universal basic model in form of an XML schema definition that includes the necessary legal and technical information.Conclusions: If electronic documents are to replace paper-based documents in patient records, they have to conform to the criteria for secure long-term archiving. The analyzed data formats are to be extended by mechanisms to guarantee the long-term security of electronic signatures. To transform large quantities of documents in a legally secure way, our basic model has to be extended for automated procedures.
Keywords: Computerized patient records; data security; documentation/standards; electronic signature; transformation